Research on Improving the Emotion and Social Relationship with Elderly with Dementia in Expressive Arts Therapy - et. al., Duan-Rong Lin , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims exploring how expressive arts therapy applied to elderly with dementia in one nursing home in Taichung Taiwan. The research is a kind of qualitative method and data was collected thought out expressive arts therapy activities designed while delivering by the art therapist and the social worker in the setting. Two groups of elderly are chosen with ten to twelve members in each, total about 20-24 members with age in between 50-90 years old. Schedule is arranged on every Tuesday for one hour of each group to engage the programme including play, music, arts for therapeutic purpose of emotional expression, released physical tense, increasing social interaction and promoting the programme in nursing home nationally. The analysis of the research includes interpersonal activities within therapeutic relationship, observation, interview by the art therapist, and report on progress of attending the activities by the social worker, and with one case study of reflection on making art works. The results of the research include the elders feel enjoy the activities, emotional wellbeing, body relaxation, interpersonal skill. Nevertheless the programme is seen to be worthwhile developing in all nursing home for elderly with dementia in Taiwan.